Clickbait Judul Berita Online dalam Pemberitaan Covid-19 - Nur Dwi Sukmono (TRANSFORMATIKA, 2021)
The development of Covid-19 news in 2020 is enough to generate public interest in reading the series of events that occurred. Covid-19 news has always been the main topic in print and online media. In one of the online media, Tribunnews.com, dated January 4, 2021 there are 47 news about Covid-19 of the 64 articles; On Detik.com (still on the same date) there are 52 news stories about Covid-19 out of 74 news; On kompas.com (still on the same date) there were 41 news about Covid-19 out of 53 news. When calculated as a whole in one week there is an average of 72.7% news about Covid-19 from the three media.This research uses descriptive qualitative method. The three most active online media in Indonesia were observed. The three online media are Tempo.co, Detik.com, and Tribunnews.com. Researchers will observe in terms of exaggeration, teasing, inflamatory, formatting, ambiguous, and wrong. These six things in a sense have a direct impact on the reader when reading the title.Through the six clickbait categories found, the online media indicated that they used clickbait in reporting COVID-19. It aims to increase the reader's curiosity through the title. After that, readers will directly click on the title to read more details about the news content. The first reason for using clickbait is profit. It is undeniable, with the movement of print media to online media, it has also shifted the way of getting profit. The second reason is the characteristics of the reader. Based on the research APJII 2020, the rate of Internet users in Indonesia mengkat up to 171.17 million. The highest Internet users in the age range 15-19 years by 91%, followed by the age of 20-24 years (88.5%) and 25-29 years (82.7%). Based on these data, the use of the internet is very massive.